Find functions \( f(x) \) and \( g(x) \) so the function \( h(x)=\frac{4}{(2 x-3)^{2}} \) can be expressed as \( h(x)=f(g(x)) \) Of(x)=\( \frac{4}{x}, g(x)=2 x-3 \) \( O f(x)=2 x-3, g(x)=\frac{4}{x} \) \( O f(x)=2 x-3, g(x)=\frac{4}{x^{2}} \) \( O f(x)=\frac{4}{x^{2}}, g(x)=2 x-3 \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To express the function \( h(x) = \frac{4}{(2x-3)^2} \) in the form \( h(x) = f(g(x)) \), we need to identify the inner function \( g(x) \) and the outer function \( f(x) \). A fitting choice is: - Let \( g(x) = 2x - 3 \) (the linear transformation that simplifies our function), - Then, \( f(x) = \frac{4}{x^2} \) (which takes the output of \( g(x) \) and feeds it into \( h(x) \)). Now let's check: if \( g(x) = 2x - 3 \), plugging it into \( f(g(x)) \) gives \( f(2x - 3) = \frac{4}{(2x - 3)^2} \), matching our original function \( h(x) \). Thus, the correct functions are \( f(x) = \frac{4}{x^2} \) and \( g(x) = 2x - 3 \). So the answer is: \( O f(x) = \frac{4}{x^2}, g(x) = 2x - 3 \) You got it right!